Self-Paced Learning Model Based on BMC for Edu-Project Entrepreneurship in Higher Education - Rochmawati; Mustiningsih; Aan Fardani Ubaidilah; Djum Djum Noor Benty; Hasna Dwi Purbaningru; Moch. Haris Purwanto; Amelia Dwi Lestari; Sri Wahyuni Eka Satria; Agustinus Hermino Suprema Putra (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2023)
The purpose of this research is to increase the self-paced learning of international/outbound students, Increase the agility of outbound student, and education-project entrepreneurship especially in National University of Laos (NUOL). This research use action research approach. This research was conducted for international student with 38 students from the Economic and Business faculties at NUOL. The data technique with On-In-On through a duo approach system, namely online and offline with locations in two countries, Indonesia and Laos with data collection technique in this research uses an unstructured questionnaire. Data processing and analysis techniques use Tabulating. The results of the study show that outbound student can improve self-paced learning by design model learning based Business Model Canvas (BMC) in higher education can implementing design their own business. This design model is effective strategy in synergizing the era of digital system contributions in building independent learning and increasing the entrepreneurial spirit of outbound students who have to survive in higher education.